Habitat Characteristics of Wreathed Hornbill (Rhyticeros undulatus Shaw, 1881) in Sokokembang Forest, Central Java, Indonesia - Wijayanti, Fahma; Apriani, Eka; Fitriana, Narti; Fajarini, Ulfah (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Wreathed hornbill is a bird species that can be a bio-indicator and has a role in forest regeneration. This study aimed to estimate the population density of the wreathed hornbill and to identify its habitat characteristics. Bird populations were counted using the Variable Circular Plot (VCP) method. Habitat characteristics were then assessed by measuring environmental factors and analyzing vegetation within 20 × 20 m plots established at foraging, roosting, and nesting sites. Data analysis involved determining individual density, distribution pattern, conducting vegetation analysis, and performing a Principal Component Analysis (PCA). Wreathed hornbill that was found are 20 ± 1.2 individuals. The population density is 7.047 individuals/km2 and has a clustered distribution pattern. The habitat of the wreathed hornbill is characterized by a vegetation composition consisting of 14 species from 8 families. Types of trees with the highest INP were Ficus mbulu (Ficus annulata) (INP 54%), Ficus krandan (Ficus sp1) (INP 46%), and Ficus bulu so (Ficus globosa) (INP 32%). There are 9 types of foraging trees, 10 species of roasting trees, and 1 nesting tree species used by the wreated hornbill. Based on PCA, wind speed and light intensity are environmental factors that have a correlation with the population density of the wreated hornbill in Sokokembang Forest.